Characterization of potential liquid fertilizers obtained by hydrothermal treatment of chicken feathers. Issue 1 (15th July 2017) - Nurdiawati, Anissa; Nakhshiniev, Bakhtiyor; Zaini, Ilman Nuran; Saidov, Nurali; Takahashi, Fumitake; Yoshikawa, Kunio
Abstract : Bio‐based fertilizers are currently gaining interest as a method for reducing the use of chemical fertilizers and as a means for safe disposal of biomass waste. Feathers, which are an abundantly available biomass and have a high N content, are a potential source of fertilizer nutrients. In this study, chicken feathers were subjected to hydrothermal treatment (HTT) with lime addition in the temperature range of 140–200°C to obtain a high N containing liquid product that can be used as a liquid fertilizer. The objective of this study was to examine the effect of HTT conditions on the feather solubilization rate and the properties of the liquid products. The results showed that HTT with a reaction temperature of 180°C, a reaction time of 30 min, feather‐water ratio of 1:5, and lime addition is sufficient to solubilize as high as 83% of the chicken feather protein. The produced liquid contained nitrogen of up to 3.4% and total amino acid content of 13.6%. These results indicate the potential utilization of soluble hydrolyzed feather obtained from the HTT process for liquid N fertilizer. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 375–382, 2018